Analisis Pengaruh Servqual Terhadap Kepuasan Serta Loyalitas Mahasiswa (Studi Kasus Pada Jurusan Teknik Mesin Di Universitas â€œXYZâ€) - Maulana, Yassyir; Astuti, Murti; Surachman, Surachman (Jurnal Rekayasa Mesin, 2012)
In the future right now, thight competition not only happens to the economic sector, but have been venturing into the education sector. Improve quality is one of the business strategies that are used to improve customer satisfaction. Customer satisfaction will be achieved if the quality of product or service to be fulfilled suit their needs. But giving satisfaction to customers is not enough and even requisite is customer loyalty. Customer loyalty in the world of education closely related to loyalty student. Loyalty student are necessary for survival and existence of a college. Student who have high loyalty is an asset to college because give positive recommendation and encourage friends, brother and other civil society to use education service that have been perceived and experienced firsthand. This research aims to analyze the influence of the SERVQUAL variables consisting of Tangible, Reliability, Responsiveness, Assurance and Empathy with variable SATISFACTION and variable LOYALTY at the engineering university â€œXYZâ€. This research was conducted by the method of survey, the data obtained through the distribution of questionnaires to 125 respondent, but respond only about 112 student. Method of sampling using Random Sampling. Data analyzed by the method of Structural Equation Modeling (SEM) using LISREL 8.80 program with Maximum Likelihood estimation. The result of this research can be concluded there was no correlation between variable SERVQUAL with variable LOYALTY, while there is a relationship between variable SERVQUAL with variabel SATISFACTION, then there is a relationship between variable SATISFACTION with variable LOYALTY. it can be concluced that, if the quality of service improved then student will be satisfied and expected with that satisfaction can create loyalty which is positive word of mouth.Keywords: SERVQUAL, Student Satisfaction, Student Loyalty.